Relationship between the cash conversion cycle and profitability : Evidence from the listed companies in the IBEX 35 (Spanish Stock Exchange) - Azcoiti Navarro, Iñigo (My University, 2021)
The research investigates the relationship between the cash conversion cycle, the elements that compose it (accounts receivables, accounts payables and inventory) and corporate profitability measured by two metrics: Return on assets and return on equity. In order to examine this relationship a series of statistical tools such as descriptive statistics and correlation matrix have been used. The scope of the study involves 26 of the 35 corporations that are listed in the Spanish Stock Exchange (IBEX 35) from a three year span (2017 to 2019). Financial data has been obtained from the company’s annual reports and from official source such as the Bolsa de Mercados y Valores (BME) to calculate the number of days of sales outstanding, and the number of days of inventory. The number of days’ accounts payables has been directly taken from the annual reports. Through the analysis carried out, the study reveals the inverse relationship between profitability and the cash conversion cycle. The analysis further looks at the different characteristics of each industry and takes into account how the cash conversion cycle varies from industry to industry depending on their operations. The study adds on to the existing literature regarding working capital and profitability by arguing through empirical evidence that an effective management of working capital is vital for a company’s success. The results show a significant inversely proportional relationship between the cash conversion cycle and the corporate profitability metrics analyzed. The research concludes that since there is in fact an inversely correlated relationship between the variables studied, and there is room for improvement in terms of working capital management in Spanish listed companies, these could implement the Chief Risk Officer figure to further manage working capital in an efficient manner.
Grado en Administración y Dirección de Empresas Mención Internacional (E-4)
Keywords: 53 Ciencias económicas; 5311 Organización y dirección de empresas; 531107 Investigación operativa